Analisis dan Perbaikan Situs Web Sekolah Menggunakan Pendekatan Goal-Directed Design (Studi Kasus: SMA Negeri 1 Pasuruan) - Yhanuar Alkhamislam; Retno Indah Rokhmawati; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
SMA Negeri 1 Pasuruan is one of the senior high school that uses the website as one of the information centers for the people. But in its use, there are still some problems found, such as the lack of updates on news content, video content that has partially cut off screen, a counseling page but does not have content so it can reduces the level of comfort of the user experience. Goal-Directed Design (GDD) is used as an appropriate step to solve these problems because it focuses on user goals that are collaborated with organizational goals. There are 6 phases of GDD namely; Research, namely conducting initial testing using the User Experience Questionnaire (UEQ) and interviews with users. Then in the Modeling phase, the process of determining the identification of user groups, organizational goals, and making persona. In the Requirements Definition phase, problem grouping, reconfirmation of recommendations for improvement to stakeholders, and designing web page information structure design using card sorting. Then the Wireframe and Refinement phase is carried out making designs and prototype designs for material comparison with the initial design. And in the last phase, Design Support is carried out UEQ testing of the solution design and compared with the results of the UEQ testing at the Research phase. The initial design test results at the Research phase obtained an average distribution of -0.39 to 0.99 (below average) . The results of testing the design of solutions have an average distribution between 1.58-2.01 converted in the benchmark data at a level above the average so that it can be said that the solution design can be a recommendation to improve the website of SMA Negeri 1 Pasuruan.